Towards the Design of Future Aircraft: A Critical Review On the Tools and Methodologies - Yaolong Liu; Siyu Zhang; Jiechao Zhang; Kexuan Yao; Mingqiang Luo; Yantao Liu (Aerospace Research Communications)
This study reviews tools and approaches developed at universities and institutes for conceptual and preliminary aircraft design. Problem, solution, and behavioral space covered by each tool are discussed and a categorization for the methods underlying the different disciplinary tools is proposed. Special attention is given to the search method, if any, embedded in or supported by each tool to explore the proliferation of Multidisciplinary Design Optimization (MDO) in aircraft design tools. The study shows that many tools are available but most are proprietary and none covers all the aspects of the conceptual and preliminary design process. MDO is only a small element in most of the tools. The review can be used for the formulation of requirements and necessities for future aircraft design tools.